The Influence of Avatar Embodiment on Time Perception - Towards VR for Time-Based Therapy - Unruh, Fabian; Landeck, Maximilian; Oberdörfer, Sebastian; Lugrin, Jean-Luc; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2021)
Psycho-pathological conditions, such as depression or schizophrenia, are often accompanied by a dysfunctional perception of time. Virtual Reality (VR) could potentially help to diagnose and maybe treat such psychosis. However, the conditions in which a VR simulation could correctly diagnose a time perception deviation are still unknown. In this paper, we present an experiment investigating the difference in time experience with and without a virtual body in VR. The process of substituting a person's body with a virtual body is called avatar embodiment. Numerous studies demonstrated interesting perceptual, emotional, behavioral, and psychological effects caused by avatar embodiment. However, the relations between time perception and avatar embodiment are still unclear. Whether or not the presence or absence of an avatar is already influencing time perception is still open to question. Therefore, we conducted a between-subjects design with and without avatar embodiment (avatar vs. no-avatar) in which healthy subjects had to wait for seven and a half minutes in a room without any distractors (e.g., no window, magazine, people, decoration) or time indicators (e.g., clocks, sunlight). Participants were unaware that they will be asked to estimate their waiting time duration as well as describing their experience of the passage of time at a later stage. Our main finding shows that the absence of a virtual body is significantly slowing down the passage of time. According to our results, we suggest including avatar embodiment in future VR time-based diagnostic and treatment tools for psychosis to avoid inducing artificial deviations of time perception.